2022
DOI: 10.21149/13584
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns of dengue and Zika incidence during the 2015-2018 outbreak of Zika in Mexico

Abstract: Objective. Evaluate spatially and temporally simultaneous presence of clusters of dengue and Zika clinical cases and their relationship with expected dengue transmission risk. Materials and methods. A classification of dengue risk transmission was carried out for whole country, and spatial autocorrelation analyses to identify clusters of confirmed clinical cases of dengue and Zika from 2015 to 2018 was conducted using Moran’s Index statistics. Results. Clusters of both diseases were identified in dengue-high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…This is known in Spain, where the virus does not currently circulate, but the regular arrival of infected people from endemic countries presents a constant risk. In addition, multiple studies in Mexico, and globally, include probable or confirmed cases as another study variable [53].…”
Section: Discussionmentioning
confidence: 99%
“…This is known in Spain, where the virus does not currently circulate, but the regular arrival of infected people from endemic countries presents a constant risk. In addition, multiple studies in Mexico, and globally, include probable or confirmed cases as another study variable [53].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, our research has limitations already pointed out in similar Mexican studies (Dzul-Manzanilla et al, 2021;Cortés-Escamilla et al, 2022). Our analyses were based in registered confirmed cases, which may flaw identifying additional hotspots in local areas with less access to health care interventions for the timely diagnosis of the disease.…”
mentioning
confidence: 85%
“…Subsequent studies showed that ZIKV is an arbovirus of the genus Flavivirus, whose main vector is the Aedes aegypti mosquito 1 . Since then, cases of ZIKV infections in humans with diverse clinical manifestations have been reported; over time, cases with more severe alterations have appeared 5,15,22 .…”
Section: Zikvmentioning
confidence: 99%